Stemmed Versus Nonstemmed Tibia in Primary Total Knee Arthroplasty: A Similar Pattern of Aseptic Tibial Loosening in Obese Patients with Moderate Varus. 5-Year Outcomes of a Randomized Controlled Trial - Mohammad, Molham M.; Elesh, Mohammed M.; El-Desouky, Ihab I. (The Journal of Knee Surgery, 2022)
Obesity is linked to early tibial tray failure after primary total knee arthroplasty (TKA) for osteoarthritis (OA), especially in patients with preoperative varus. This study compared standard and stemmed tibiae TKAs in patients with class I and II obesity with varus deformity. Between April 2013 and June 2020, a prospective study was conducted including patients with end-stage OA, body mass index between 30 and 40 kg/m2, and varus <15 degrees. Patients were randomly assigned to TKAs with either standard or long-stemmed tibiae and evaluated 5 years after surgery using the Knee Society Scoring (KSS). The knee society and modified radiographic evaluation systems were used for radiological evaluation. In total, 264 TKAs were performed in 264 patients (134 in the standard group and 130 in the stemmed group). The mean preoperative hip–knee–ankle angles for the standard and stemmed groups were 8.2 ± 3.2 degrees/varus and 9 ± 2.9 degrees/varus, respectively (p = 0.2), which improved to 5.1 ± 3 degrees/valgus and 5 ± 3.5 degrees/valgus after surgery (p = 0.52). There was no statistically significant difference between the objective KSS (92 vs. 92.9; p = 0.84) and the functioning KSS (73.4 vs. 74.8; p = 0.28). There were no aseptic loosening cases or radiographic differences. In-group analysis revealed significant outcomes differences in both groups if preoperative varus was >10 degrees irrespective of the stem design (p < 0.0001). Complications occurred in two patients; one with a late infection and one had a stem-related tibial fracture. Standard tibia TKAs yielded comparable results in obese patients to long-stemmed tibias. No aseptic tibial loosening was observed regardless of stem type, and worse clinical outcomes were associated with greater varus.Clinical trial registry: registered at http://www.researchregistry.com (researchregistry5717).Level of Evidence II; a prospective randomized trial.
Keywords: obesity; primary total knee arthroplasty; stemmed tibia; aseptic loosening